Respuesta :

To solve for y, you need to isolate/get the variable "y" by itself in the equation:

a(n + y) = 10y + 32      First distribute a into (n + y)

(a)n + (a)y = 10y + 32

an + ay = 10y + 32        Subtract an on both sides

an - an + ay = 10y + 32 - an

ay = 10y + 32 - an      Subtract 10y on both sides to get "y" on one side of the equation

ay - 10y = 10y - 10y + 32 - an

ay - 10y = 32 - an       Now take out the y in (ay - 10y)

y(a - 10) = 32 - an       Divide (a - 10) on both sides to get "y" by itself

[tex]\frac{y(a-10)}{(a-10)} =\frac{32-an}{(a-10)}[/tex]

[tex]y=\frac{32-an}{a-10}[/tex]

Otras preguntas